EVALUATION OF THE MOLECULAR-BIOLOGICAL PROPERTIES OF HUMAN ROTAVIRUS A STRAIN WA - K. M. Khametova; K. P. Alekseev; A. G. Yuzhakov; L. V. Kostina; S. A. Raev; M. I. Musienko; A. N. Mukhin; T. I. Aliper; G. K. Vorkunova; T. V. Grebennikova (Вопросы вирусологии, 2019)
Introduction. Rоtaviruses are amоng the leading causes of severe diarrhea in children all over the Wоrld. Vaccination is considered to be the mоst effective way to cоntrоl the disease. Currently available vaccines for prevention of rоtavirus infection are based on live attenuated rotavirus strains human оr animal origin. Objectives and purposes. The aim of this investigation was to study the biological and genetic properties of an actual epidemic human rotavirus A (RVA) strain Wa G1P[8] genotype. Material and methods. RVA Wa reproduction in a monolayer continuous cell lines, purification and concentration of RVA antigen, PAAG electrophoresis and Western-Blot, electrophoresis of viral genomic RNA segments, sequencing. Results. Human RVA G1P[8] Wa strain biological and molecular genetic properties were assessed in the process of the adaptation to MARC145 continuous cell line. Cell cultured RVA antigen was purified, concentrated and then characterized by the method of PAAG electrophoresis and immunoblot. To verify RVA Wa genome identity, electrophoresis of viral genomic RNA segments was performed. The lack of accumulation of changes in the RVA Wa genome during adaptation to various cell cultures and during serial passages was demonstrated by sequencing fragments of the viral genome. Conclusion. RVA Wa strain is stable, it possesses high biological activity: it has been successfully adapted to the MARC145 cell line and RVA Wa virus titer after the adaptation reached 7,5-7,7 lg TCID50/ml. The identity of the cultivated RVA to the original strain Wa G1P[8] was confirmed.